Deteksi Gen Staphylococcal Enterotoxin Type A (SEA) dan Koagulase (coa) Staphylococcus aureus Pada Susu Sapi Mentah dari Peternakan Sapi Perah Wilayah Wonocolo Surabaya - Endah Prayekti; Afrida Cahya Maharani; Ika Nur Aini (Biotropic : The Journal of Tropical Biology, 2025)
Staphylococcus aureus is a pathogen that often contaminates raw cow's milk and involves various virulence factors during the tissue infection process such as enterotoxins and coagulase enzymes. Staphylococcal Enterotoxin Type A (SEA) and coagulase enzymes (coa) are important virulence factors of Staphylococcus aureus. SEA is a very potent gastrointestinal superantigen toxin and the presence of the SEA gene of Staphylococcus aureus in milk indicates a potential risk of food poisoning. Staphylococcus aureus is the most invasive species because it has a coagulase enzyme encoded by the coa gene as a defense against neutrophil white blood cell phagocytosis and contributes to the infection process. The purpose of this study was to detect the virulence factors of the SEA gene and coa gene of Staphylococcus aureus bacteria in raw cow's milk from farms in Wonocolo Surabaya to assess the safety of milked milk. The research method used was qualitative with a descriptive observational research type. Conventional microbiological testing of a total of 24 bacterial isolates obtained 5 isolates identified as Staphylococcus aureus. Staphylococcus aureus bacterial DNA isolates were analyzed molecularly using the Polymerase Chain Reaction (PCR) method and obtained 40% of positive samples for the SEA gene and 100% of negative samples for the coa gene. The results of coa gene detection showed negative even though the conventional test tube results obtained positive coagulation results. The failure of coa gene amplification in isolates was likely because this study used primers based on literature without designing its own primers and did not optimize PCR before analyzing samples.